1996
DOI: 10.1080/01411599608207838
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies for ZnxMg0.8-xNi0.2Fe2O4 ferrites

Abstract: A series of samples of the system ZnIMgo.8-,N~.2Fe~04 (with x=0,0.2,0.4,0.6 and 0.8), was prepared using the usual ceramic technique. The samples were studied using X-ray diffraction, DTA, TG, TGA and IR spectroscopy. The lattice constant, radius of tetrahedral ion, X-ray density and measured bulk density are found to increase while porosity decreases as zinc ion content increases. Both TG and TGA spectra show two exothermic phases at the magnetic T, and Curie T, transition temperatures while DTA does not indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…It is observed that the position of the band 2 shift towards the lower frequency, which confirms the occupancy of Sm 3+ ions on the octahedral site. The similar results have been reported for rare-earth element substituted for Ni-Zn [18], Cu-Cd [19], and Zn-Ni-Mg ferrites [3]. This may be due to atomic mass and volume of the dopant, which affect Fe-O distances on octahedral sites, suggesting that Sm 3+ ions occupied octahedral lattice sites.…”
Section: Ir Absorption Studiessupporting
confidence: 80%
See 2 more Smart Citations
“…It is observed that the position of the band 2 shift towards the lower frequency, which confirms the occupancy of Sm 3+ ions on the octahedral site. The similar results have been reported for rare-earth element substituted for Ni-Zn [18], Cu-Cd [19], and Zn-Ni-Mg ferrites [3]. This may be due to atomic mass and volume of the dopant, which affect Fe-O distances on octahedral sites, suggesting that Sm 3+ ions occupied octahedral lattice sites.…”
Section: Ir Absorption Studiessupporting
confidence: 80%
“…Another low frequency band 4 appears for all the compositions (except for composition x = 0.8 for y = 0.05, x = 0.2, 0.4 for y = 0.1), which depends on the mass of the divalent tetrahedral cation and is related to some type of vibrations involving a displacement of tetrahedral cation [24]. It is observed that the intensity and band position are the composition dependent [3,21].…”
Section: Ir Absorption Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between absorption bands n 1 and n 2 is due to changes in bond length (Fe 3þ -O 2À ) at tetrahedral and octahedral sites [24]. Here we can observe slight change in band position in n 1 and n 2 this difference is due to the method of preparation, grain size and porosity can influence in locating the band position [25,26]. The difference between the spectra upon increasing the amount of dopant elements this is may be due to the increase of the amount of undesired Fe, Gd and Sm oxides in material.…”
Section: Structural Analysis By X-ray Diffractometermentioning
confidence: 81%
“…Here we can observe slight change in band position in ν 1 and ν 2 this difference is due to the method of preparation, grain size and porosity can influence in locating the band position [23]. It can be seen that the absorption band ν 1 not shown any splitting or shoulders and hence the possibility of Fe 2+ ions at A-sites is ruled out [24].…”
Section: +mentioning
confidence: 99%